International Students and Scholars in the United States: Coming From Abroad - Saha, Neete (Journal of International Students, 2014)
International students and scholars in the United States: Coming from abroad is a well-written, well-researched, and well-timed monograph. In pursuit of higher education, international students have continued to attend colleges and universities in the United States of America in spite of the educational, emotional, and cultural issues. According to the Institute of International Education (IIE), 723, 277 international students and more than 115,000 international scholars matriculated in American colleges and universities in 2010/2011 (pp. 4-9). The editors, Heike Alberts and Helen Hazen, have not only provided readers with an opportunity to learn about international students and scholars from Asia, Africa, and Europe but have also addressed critical issues faced by the international students and scholars in the United States.